2019
DOI: 10.1021/acs.analchem.8b03964
|View full text |Cite
|
Sign up to set email alerts
|

Split Dapoxyl Aptamer for Sequence-Selective Analysis of Nucleic Acid Sequence Based Amplification Amplicons

Abstract: Hybridization probes have been used for the detection of single nucleotide variations (SNV) in DNA and RNA sequences in the mix-and-read formats. Among the most conventional are Taqman probes, which require expensive quantitative polymerase chain reaction (qPCR) instruments with melting capabilities. More affordable isothermal amplification format requires hybridization probes that can selectively detect SNVs isothermally. Here we designed a split DNA aptamer (SDA) hybridization probe based on a recently repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 41 publications
(82 reference statements)
0
36
0
Order By: Relevance
“…These strands have low affinity to the dapoxyl dye unless specific targets bind to adjacent positions and form binding sites for the dye to generate fluorescent signals. In this work, they used these strands to successfully distinguish a fragment of the inhA gene of Mycobacterium tuberculosis from its single-base variant and detect 10 nM of Z-147 RNAs (a fragment of the ZIKV envelope gene) extracted using Trizol LS ( Kikuchi et al, 2019 ). With portable fluorometers, this probe has the potential to achieve POC diagnosis.…”
Section: Nucleic Acid Sequence-based Amplificationmentioning
confidence: 99%
“…These strands have low affinity to the dapoxyl dye unless specific targets bind to adjacent positions and form binding sites for the dye to generate fluorescent signals. In this work, they used these strands to successfully distinguish a fragment of the inhA gene of Mycobacterium tuberculosis from its single-base variant and detect 10 nM of Z-147 RNAs (a fragment of the ZIKV envelope gene) extracted using Trizol LS ( Kikuchi et al, 2019 ). With portable fluorometers, this probe has the potential to achieve POC diagnosis.…”
Section: Nucleic Acid Sequence-based Amplificationmentioning
confidence: 99%
“…Dynamics parameters on the dissociation process of split aptamer/VEGF 165 complex, such as the binding lifetime τ (=1/k off ), k off , and x β , was estimated according to Equation (1). As shown in It demonstrated that split aptamer of VEGF 165 still exhibited high affinity to its target.…”
Section: Effect Of Concentration On the Binding Of Split Aptamer Anmentioning
confidence: 99%
“…Split aptamer was obtained by dividing the intact aptamer, which could self‐assemble to produce a positive signal when the target was present. They had a good enhancement effect in enhancing signal‐to‐background ratio and reducing nonspecific signal because of their excellent merit in avoiding steric hindrance. Thus, the application of split aptamer was various, such as biosensing, bioimaging, drug delivery, and theranostics …”
Section: Introductionmentioning
confidence: 99%
“…Such RNA-based signaling elements are present in malachite green/RNA aptamer pair [15,16] and GFP chromophore analogue DFHBI/split spinach aptamer pair [17,18]. Despite increased chemical and biological stability of DNA aptamers compared to RNA ones, the only example of such a biosensor based on light-up dye-DNA aptamer pair as "signaling element" is dapoxyl dye/DAP-10-42 for thrombin and ATP detection [19] and "split" DAP-10 variant for nucleic acids analysis [20]. Several examples are devoted to label-free sensors utilizing G-quadruplex DNAs and their light-up ligands as "signaling elements", including zinc(II)-protoporphyrin IX [21], thioflavin T [22], iridium(III) complexes [23] and crystal violet [24].…”
Section: Introductionmentioning
confidence: 99%